Correlation of Learning Systems with Student Engagement and Learning Outcomes - Pradana, Mochamad Desta; Setyosari, Punaji; Ulfa, Saida; Degeng, Made Duananda Kartika (Al-Hayat: Journal of Islamic Education, 2024)
Ubiquitous Project Based Learning (UPBL) offers learning opportunities that are not limited by time and place, adapts to students' level of mastery, and creates learning communities where students can engage with each other while working on learning projects. UPBL actively contributes to achieving learning goals as best as possible. This research aims to determine the relationship between Ubiquitous Project Based Learning (UPBL) and Self-Regulated Learning (SRL) with student involvement and to choose the relationship with learning outcomes. This research uses a one-group pretest-posttest design. The parametric statistical test analysis technique of Pearson product-moment correlation was used to calculate the research data findings. The output of data calculations using SPSS is correlation data between Ubiquitous Project Based Learning (UPBL) and Self-Regulated Learning (SRL) students with student involvement and learning outcomes which is known to indicate a significant relationship between UPBL and SRL students, with student involvement and learning outcomes. , which is 0.000 and 0.005, which is smaller than the value of 0.05, it can be concluded that there is a significant relationship between UPBL and SRL students with student engagement and learning outcomes. The research results show that UPBL is substantially related to SRL regarding student engagement and learning outcomes.